(3QSGdI Edi LdGdI GdSdWGf ehdGj ESeGYjds - (3GdMSf Hf eSYhO Hf eMeO, CHh Ydj, fhQ GdOjf GdjhSj,J (B1102 (3g` s ((3GdSjO CMeO Hf eMeO GdfejTj GdMSfj s)
(3ChdgG (B:s
(3eQcR GdeLO hGdKfGA , hMGQR GdMeO hGdKfGA, hjfHhY GdeMGSf hGdeaGNQ s
(3BNQgG (B:s
(3cGfJ GdeMHI GdOfjGhjI CXgQ BKGQkG hCcKQ KeGQkG, hGdfGbO HUjQ, hEdjg GdeUjQ s
(3Vef eLehY , JQJjHgG (B: (3ef U H (B13 - (3U H (B36s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B237 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B294s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B193 ; (3agQSJ GdNRGfI GdYGeI HGdQHGW (B- (3GdLRA (B2 - (3U (B127 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs